2007
DOI: 10.33584/jnzg.2007.69.2674
|View full text |Cite
|
Sign up to set email alerts
|

High sugar ryegrasses for livestock systems in New Zealand

Abstract: There has been mounting interest over the proposed production and environmental benefits from using perennial ryegrass cultivars bred to have higher water soluble carbohydrate content (high sugar grasses). Here, we objectively review published evidence, from the EU and New Zealand, of the effects of these on milk yield per cow, liveweight gain in sheep, N utilisation and wider trophic interactions. The literature reveals substantial variation in animal responses, though some of the uncertainty in interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 43 publications
2
59
2
Order By: Relevance
“…Cows fed alfalfa with greater WSC concentrations (Brito et al 2008(Brito et al , 2009 or highsugar grasses (Miller et al 2001) utilized N more efficiently and produced more milk. A WSC:CP ratio above 0.70 has been proposed to improve dietary N use for milk production and to reduce N losses in urine (Edwards et al 2007). In our study, the average WSC:CP ratio across the three harvests and the 2 post-seeding years was 0.65 for the alfalfa monoculture and 0.79 for the alfalfaÁtimothy mixture.…”
Section: Alfalfa Vs Alfalfa á Timothy Mixturementioning
confidence: 51%
“…Cows fed alfalfa with greater WSC concentrations (Brito et al 2008(Brito et al , 2009 or highsugar grasses (Miller et al 2001) utilized N more efficiently and produced more milk. A WSC:CP ratio above 0.70 has been proposed to improve dietary N use for milk production and to reduce N losses in urine (Edwards et al 2007). In our study, the average WSC:CP ratio across the three harvests and the 2 post-seeding years was 0.65 for the alfalfa monoculture and 0.79 for the alfalfaÁtimothy mixture.…”
Section: Alfalfa Vs Alfalfa á Timothy Mixturementioning
confidence: 51%
“…However, such cultivars might not consistently express the high sugar trait under certain environments [8,35]. Furthermore, high sugar grasses may have lower DM yields than standard cultivars [54][55][56]. Therefore, in order to assess the actual environmental benefit of grazing systems that either use these improved cultivars or apply pasture management regimes aimed to enhance forage WSC concentrations, an accurate evaluation of their nutritional value is required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, both methane production per unit organic matter intake and the proportion of N intake that is excreted as urine are dependent on perennial ryegrass genotype (Miller et al , 2001; Lovett et al , 2006). Here we focus on the development through selective breeding of perennial ryegrass genotypes with high water‐soluble carbohydrate content (‘high‐sugar’ grasses) (Humphreys, 1989; Miller et al , 2001; Lee et al , 2002; Edwards et al , 2007 a,b ). The hypothesis is that by improving the balance and supply of energy and protein in the rumen, greater N capture may occur.…”
Section: Positive Plant Microbial Interactions With Potential For Devmentioning
confidence: 99%
“…These gains were shown to come via greater capture of microbial N in the rumen and greater passage of microbial protein to, and absorption of amino acids from, the small intestine (Merry et al , 2003). Edwards et al (2007 a,b ) reviewed data from trials carried out in the UK, Holland, New Zealand and Australia that assessed the effects of high water‐soluble carbohydrate ryegrass cultivars on milk yield per cow, N utilisation and wider trophic interactions. The literature revealed substantial variation in animal responses, although much of this uncertainty was resolved by combining the data from multiple trials, which showed a continuum of response to diet ‘quality’, specifically, when related to a tissue water‐soluble carbohydrate to crude protein ratio.…”
Section: Positive Plant Microbial Interactions With Potential For Devmentioning
confidence: 99%